Severe Acute Respiratory Syndrome Coronavirus 2 Transmission in a Georgia School District—United States, December 2020–January 2021. (17th April 2021) - Gettings, Jenna R; Gold, Jeremy A W; Kimball, Anne; Forsberg, Kaitlin; Scott, Colleen; Uehara, Anna; Tong, Suxiang; Hast, Marisa; Swanson, Megan R; Morris, Elana; Oraka, Emeka; Almendares, Olivia; et al.
Abstract: Background: To inform prevention strategies, we assessed the extent of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and settings in which transmission occurred in a Georgia public school district. Methods: During 1 December 2020–22 January 2021, SARS-CoV-2–infected index cases and their close contacts in schools were identified by school and public health officials. For in-school contacts, we assessed symptoms and offered SARS-CoV-2 reverse-transcription polymerase chain reaction (RT-PCR) testing; performed epidemiologic investigations and whole-genome sequencing to identify in-school transmission; and calculated secondary attack rate (SAR) by school setting (eg, sports, elementary school classroom), index case role (ie, staff, student), and index case symptomatic status. Results: We identified 86 index cases and 1119 contacts, 688 (61.5%) of whom received testing. Fifty-nine of 679 (8.7%) contacts tested positive; 15 of 86 (17.4%) index cases resulted in ≥2 positive contacts. Among 55 persons testing positive with available symptom data, 31 (56.4%) were asymptomatic. Highest SARs were in indoor, high-contact sports settings (23.8% [95% confidence interval CI, 12.7%–33.3%]), staff meetings/lunches (18.2% [95% CI, 4.5%–31.8%]), and elementary school classrooms (9.5% [95% CI, 6.5%–12.5%]). The SAR was higher for staff (13.1% [95% CI, 9.0%–17.2%]) vs student index cases (5.8% [95% CI, 3.6%–8.0%]) and for symptomatic (10.9% [95% CI, 8.1%–13.9%]) vs asymptomatic index cases (3.0% [95% CI, 1.0%–5.5%]). Conclusions: Indoor sports may pose a risk to the safe operation of in-person learning. Preventing infection in staff members, through measures that include coronavirus disease 2019 vaccination, is critical to reducing in-school transmission. Because many positive contacts were asymptomatic, contact tracing should be paired with testing, regardless of symptoms. Abstract : We assessed severe acute respiratory syndrome coronavirus 2 transmission in a Georgia school district using in-depth epidemiologic investigations and whole-genome sequencing. In-school transmission occurred primarily when the index case was from an indoor sports setting, was a staff member, or had symptoms.